A survey of hysterectomies in young patients in Eastern Uttar Pradesh: are the wombs being removed unnecessarily? - Rani, Anjali; Mir, Heena; Mahajan, Neha; Bhushan, Ravi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: There are reports of unnecessary hysterectomies in young patients in some parts of Eastern Uttar Pradesh and adjoining regions. This study was conducted to know the indications of hysterectomies done at less than 35 years of age. Methods: This study was conducted in the outpatient Department of Gynaecology and Obstetrics, Sir Sundar Hospital, Institute of Medical Sciences, Banaras Hindu University Varanasi over a period of one year. Hysterectomised patients with age less than 35 years were included in the study. After getting an informed consent, a detailed history was taken, patient’s past medical record was reviewed and their socio-demographic profiles, indication for hysterectomy and any surgical complications were recorded. Statistical analysis of data was done using SPSS and results were recorded as mean and percentage. Results: One hundred patients were included in the study over a period of one year. Mean age of the study population was 28 years. The 32% patient were below 25 years of age, 44% were between 25 to 30 years of age whereas 24% were in the age group of 30 to 35 years. Unevaluated Vaginal discharge (28%) and pain in pelvic region (25%) were the main indication for hysterectomy. Menstrual abnormalities (13%), asymptomatic uterine fibroid (12%), small functional ovarian cyst (10%) and abnormal colposcopic images (12%) were other indications. Conclusions: There is a high prevalence of unnecessary hysterectomies in eastern part of Uttar Pradesh, India. Such practice must be discouraged and stopped. Public awareness, adherence to medical ethics and strict action against those involved in medical malpractice would be helpful in decreasing the number of unnecessary hysterectomies in the young women.